Literature Review: Perbandingan Fecal Immunochemical Test dan Fecal Calprotectin dalam Monitoring Pasien Kolitis - Naufal Nathan Arif Hitam; Agung Ary Wibowo; Rahmiati Rahmiati; Hery Poerwosusanta; Dewi Indah Noviana Pratiwi (Homeostasis, 2021)
Abstract: Colitis is a group of inflammatory diseases in colon with frequent of recurrences. Non-invasive detection methods are needed to evaluate inflammatory activity and mucosal healing in order to reduce the risk of recurrence and complications of irreversible tissue damage in colitis. Stool markers such as the fecal immunochemical test (FIT) and fecal calprotectin (Fcal) are an alternative as a simple, inexpensive, and non-invasive test for detecting inflammation in colon. The purpose of this paper is to compare the FIT and Fcal in monitoring colitis patients. This paper was done using the literature review method. Search for articles through the Pubmed and Google Scholar databases using the keyword "fecal immunochemical test AND fecal calprotectin AND colitis". Articles analyzed in English and published in the last 10 years. The results of a review of 17 articles published in this literature review found that Fcal was superior in detecting active inflammation in colitis, while FIT was superior in detecting mucosal healing, and both were able to predict recurrence in colitis. Therefore, a strategy is needed to use both examinations based on the patient's condition. If active inflammation is found in the patient, then Fcal examination is required to monitor active inflammation of the disease. When the patient is in clinical remission, FIT is needed to monitor mucosal healing and predict the risk of recurrence. Keywords: colitis, fecal immunochemical test, fecal calprotectin Abstrak: Kolitis merupakan kelompok penyakit inflamasi kolon yang sering mengalami kekambuhan. Diperlukan metode pemeriksaan non invasif untuk mengevaluasi aktivitas inflamasi dan mucosal healing agar mengurangi risiko kekambuhan dan komplikasi kerusakan jaringan yang irreversible pada kolitis. Pemeriksaan feses seperti fecal immunochemical test (FIT), dan fecal calprotectin (Fcal) menjadi alternatif sebagai pemeriksaan sederhana, murah, dan non invasif dalam mendeteksi inflamasi pada kolon. Tujuan penulisan ini untuk membandingkan FIT dan Fcal dalam memonitoring pasien kolitis. Penulisan ini dilakukan dengan metode literature review. Pencarian artikel melalui database Pubmed dan Google Scholar dengan menggunakan kata kunci “fecal immunochemical test AND fecal calprotectin AND colitis”. Artikel yang di analisis menggunakan Bahasa Inggris dan dipublikasikan dalam 10 tahun terakhir. Hasil review terhadap 17 artikel yang dimuat dalam literature review ini didapatkan Fcal unggul dalam mendeteksi inflamasi aktif pada kolitis, sedangkan FIT unggul dalam mendeteksi mucosal healing, dan keduanya mampu memprediksi kekambuhan pada kolitis. Dengan demikian diperlukan strategi untuk menggunakan kedua pemeriksaan berdasarkan kondisi pasien. Jika pada pasien ditemukan inflamasi aktif, maka diperlukan pemeriksaan Fcal untuk memantau inflamasi aktif penyakit. Saat pasien dalam keadaan remisi klinis, FIT diperlukan untuk memantau mucosal healing dan memprediksi risiko kekambuhan. Kata-kata kunci:  kolitis, fecal immunochemical test, fecal calprotectin